Distributional Impacts of an Environmental Tax Shift: The Case of Motor Vehicle Emissions Taxes - Walls, Margaret; Hanson, Jean (School of Management Working Papers, 1996)
Policymakers are currently looking more favorably on economic incentive approaches to reducing pollution, yet the enthusiasm for such approaches on efficiency grounds is usually tempered by concerns over equiqty, particularly with policies focusing on motor vehicles. In this paper, we assess the distributional impacts of vehicle fees based on (i) annual emissions, (ii) emission rates, in grams per mile, and (iii) annual miles travelled. We find that all three fees appear to be regressive, particularly on the basis of annual household income, but also on the basis of a constructed "lifetime income" measure. Emissions rate-based fees are the most regressive because poorer households often own older, dirtier vehicles. If the fees are used to substitute for existing vehicle registration fees, however, none of the three fees looks markedly different on a lifetime income basis from existing registration fees. This highlights one of the potential benefits of using a tax shift, rather than a tax increase, to help the environment.